(untitled) (Acta Scientiarum. Language and Culture, 2015)
O Ateneu (1st ed. 1888), by Raul Pompéia, and Manhã submersa (1st ed. 1954), by Vergílio Ferreira, are two novels in which the imposing educational procedures of each historical period are rendered problematic, in spite of their apparently common and strong dislike for the social standardization their discourses tend to imply. In this regard, assuming a thematic-comparative point of view, the present work seeks to analyze how the reaction to these discourses are carried out by each of those novels in order to evaluate and propose afterwards a synthesis of both Raul Pompéia’s and Vergílio Ferreira’s individual views on the matter.